Causes of Problem during Implementing Learner-Centered Instruction (LCI) Paradigm in EFL Classroom - Absharini Kardena; Putri Meldia; Elda Selja Putri; Annisah (Journal of English Development, 2022)
This research was conducted because of the high level of challenges and problems faced by the English teachers and their students during implementing learner-centered instruction paradigm. This research aims at analyzing the causes of any difficulties faced by the English and the students when they impellemented LCI in their English class. The researcg was qualitative research by using observation and interview as the instruments of the research. The research involved English teacher s and the students in one of Islamic senior high school in Solok region. Based on analyzing the data, it was found that there have been several causes why the teachers and students got difficulties in implementing LCI in their class, such as the lack of training got by the English teachers, school regulation related to the capacity of students in one class and students’ perception which was still highly depend on teachers in their learning process.